If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2x + 1) = -36 Reorder the terms: 2(1 + 2x) = -36 (1 * 2 + 2x * 2) = -36 (2 + 4x) = -36 Solving 2 + 4x = -36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 4x = -36 + -2 Combine like terms: 2 + -2 = 0 0 + 4x = -36 + -2 4x = -36 + -2 Combine like terms: -36 + -2 = -38 4x = -38 Divide each side by '4'. x = -9.5 Simplifying x = -9.5
| (X)(3x-5)=0 | | 29x-3=13y-17 | | -4x-6(1+3x)=-3x+32 | | 4x-5/3=3x-4/2 | | 7x+27=24 | | 40+4x=8x-(8-4x) | | 2(3k-7)=2k+4+k+12 | | 5x-6y=-142 | | 9x/6=12 | | 3.26x+9=10.6276+3x | | x+4[x+5]=40 | | 4(2x-1.5)=-4 | | 7y=5y+24 | | 3x+22+2x+8=180 | | 8x-2=-14 | | -(8-x)+6=13 | | 6x+9=10(3x+6) | | 1/4k=3/8kk-1/4 | | 5x+3x+2=90 | | 6k-14=3k+16 | | 1-6k=8-6k | | 5.5(x-3)=-0.5+31.5 | | -2(x-2)+x=-2 | | 10=0.5a | | y+1.4=-1.4 | | 4a+2b+18=22 | | 6/7x-8/7=9 | | (x^(1/3)*y^(1/5))^15 | | -5n-5=2n-2-6n | | -4(x-2)+x=-22 | | 3(11x+8)=33x-4 | | -3(t-5)+9t=4t-3 |